(untitled) (The International Journal of Educational Sciences and Arts, 2025)
Objectives: The current study aims to determine the degree to which University students with special needs have psychological resilience and hardness. Methodology: The study adopts a descriptive approach, using a questionnaire comprising (29) items, were divided into two themes: the first: psychological resilience included (10) items; the second: psychological hardness, included (19) items. The questionnaire was administrated to a sample of (69) special needs students. Results: The findings of the study reveal that the degree to which students with special needs had psychological resilience and hardness at the University was generally average, the psychological resilience was the first level, with an average of (3.42 per cent). The items were in the high and medium degrees for psychological resilience and hardness.The results also showed that there were no statistically significant differences in the degree to which students with special needs had psychological resilience and hardness depending on the variables: gender, type of disability, while the difference was a statistical function of the college variable and was in the interest of the Faculty of Arts and Educational Sciences when comparing the average to the mathematical average of the business college only. Conclusion: It has been noted that, in general, that the students with special needs have had moderate psychological resilience and hardness.